2018
DOI: 10.1177/0954406218813383
|View full text |Cite
|
Sign up to set email alerts
|

Novel robust controller design for load sway reduction in double-pendulum overhead cranes

Abstract: It is seen that when the hook mass is larger than the load mass or the load has distributed mass property, the load sway of the crane system presents as double-pendulum effect. In this situation, crane system has two different natural frequencies so that the sway characteristic becomes more complex and greatly increases the difficulty of the dynamic performance analysis and controller design. Moreover, the rope length changes significantly affect the stability and control performance of the crane system. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Recently, some scholars have proposed a lot of methods for the double‐pendulum load sway suppression problem in crane systems . Jaafar et al presented a novel model reference command shaping approach to deal with the vibration reduction problem in a double‐pendulum overhead crane system .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some scholars have proposed a lot of methods for the double‐pendulum load sway suppression problem in crane systems . Jaafar et al presented a novel model reference command shaping approach to deal with the vibration reduction problem in a double‐pendulum overhead crane system .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some scholars have proposed a lot of methods for the double-pendulum load sway suppression problem in crane systems. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Jaafar et al presented a novel model reference command shaping approach to deal with the vibration reduction problem in a double-pendulum overhead crane system. 38 In addition, other similar input shaping-based methods were also reported in other works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an input-shaping-based SIRMs fuzzy approach was reported in [37]. Ouyang et al reported two novel sliding-mode based approaches and a simple LMI-based robust method [38][39][40]. A nonlinear quasi-PID scheme and an adaptive nonlinear controller were applied to overhead cranes in [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, although open-loop approaches were introduced in [27][28][29][30][31][32][33][34], accurate crane models were always needed. On the other hand, too complicated algorithms were adopted in [35][36][37][38][39][40][41][42] to achieve good robust or adaptive performance. Moreover, different from the load sways of double-pendulum overhead cranes which were dealt with in the most existing literatures [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], the double pendulums in the rotary crane system are both conical pendulums, and the system characteristics are more complex.…”
Section: Introductionmentioning
confidence: 99%